Approximation of Fixed Points for Generalized Nonexpansive Maps and Application - Sangita Yadav; Dr Sarita; Dr. Prateek Mor; Dr. Pinki (Utilitas Mathematica, 2025)
In this article, we demonstrate strong convergence results of a map on a closed, bounded and convex subset of a CAT(0) space, satisfying the (RCSC)-condition using AP iterative scheme. By using the AP iterative scheme, we can find the solution of differential and inte- gral equations. The outcome we acquire improves and broadens numerous recent findings in the literature. Finally, a numerical example is also provided of a mapping which pleases the (RCSC)-condition but fails to meet condition (C).